INVESTIGATION OF STUDENTS’ PSYCHOLOGICAL ASPECTS ON ACITIVITY BASED LEARNING IN MATHEMATICS: A CASE STUDY IN SRI LANKA - Wijethunga, WWMRGKSB; Chandrasena, WD (International Journal of Research -GRANTHAALAYAH, 2019)
Mathematics is the foundation of Science and Technology. The people cannot apart from mathematics in day to day life. Thus being “mathematically literate” will no longer be just an advantage but an absolute necessity. Despite the interest towards mathematics of school students is particularly low. It shows the poor performance of students in G.C.E. (O/L) examination. This study examines the students’ self-concepts and motivation as factors that may influence students’ performance and aspirations on Activity Based Learning (ABL) of mathematics in Sri Lanka. The results clearly indicate that ABL has developed students’ self-concepts, motivation, aspirations and performance.